2013
DOI: 10.3390/ijms141020443
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Melanogenesis by Gallic Acid: Possible Involvement of the PI3K/Akt, MEK/ERK and Wnt/β-Catenin Signaling Pathways in B16F10 Cells

Abstract: Gallic acid is one of the major flavonoids found in plants. It acts as an antioxidant, and seems to have anti-inflammatory, anti-viral, and anti-cancer properties. In this study, we investigated the effects of gallic acid on melanogenesis, including the activation of melanogenesis signaling pathways. Gallic acid significantly inhibited both melanin synthesis and tyrosinase activity in a dose- and time-dependent manner, and decreased the expression of melanogenesis-related proteins, such as microphthalmia-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(91 citation statements)
references
References 40 publications
1
88
0
2
Order By: Relevance
“…Cytochrome P450 is considered as a key participant in the progression of lung cancer and a potentially valuable target for anticancer drug [31]. It has been reported that the MEK/ERK, PI3K/Akt, and Wnt/β-catenin pathways were involved in the melanogenesis signaling cascade [32]. The DEGs in these pathways might be involved in the progress of CSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome P450 is considered as a key participant in the progression of lung cancer and a potentially valuable target for anticancer drug [31]. It has been reported that the MEK/ERK, PI3K/Akt, and Wnt/β-catenin pathways were involved in the melanogenesis signaling cascade [32]. The DEGs in these pathways might be involved in the progress of CSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Analytical Instrument of Active Component 1 H (400 MHz) and 13 C (100 MHz) NMR spectra were recorded with a JEOL ECX 400 spectrometer with tetramethylsilane as an internal standard. The high-resolution MS were obtained using a LC/MSD TOF-G1969A (Agilent Technologies, Santa Clara, CA, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…12) Recently, it was reported that melanogenesis is controlled by various intracellular signaling molecules such as cAMP/protein kinase A (PKA), phosphoinositide 3-kinase (PI3K)/Akt, and ras/mitogen-activated protein kinases (MAPK). 13) cAMP/PKA regulates the expression level of MITF, 14) and ras/MAPK enhances transcriptional activity by promoting phosphorylation of MITF. 15) Experiments using inhibitors suggested that the PI3K/Akt pathway is also involved in melanogenesis.…”
mentioning
confidence: 99%
“…Only several skin-lightening compounds have demonstrated the ability to inhibit tyrosinase in addition to activating or inhibiting intracellular signal cascades leading to the transcriptional inhibition of melanin synthesis genes, such as haginin A (Kim et al [10]), gallic acid (Su et al [12]), and hydroquinone (Inoue et al [25]). These studies focused on the MAPK and Akt signaling pathways.…”
Section: Mapk Signaling Pathway In Melanogenesismentioning
confidence: 99%